System of acquisition and real time display of images for processing - Corkidi, B. G.; Solar, S. A.; Garcia, M. C. (Revista Mexicana de Ingenieria Biomedica, 2018)
We designed a system that acquires and displays in video time (1/30 sec) four images of 256 x 256 minimum image elements (PIXEL) with 128 levels of gray, or an interlaced image of 512 x 512 PIXELS with 7 bits of depth. The interface of this system was also designed to an 8-bit microcomputer and some tests of digital image processing performed in this equipment such as digital subtraction and contrast enhancement by the method of "Linearization of Histograms"